Optimization of Bearing Capacity of Sandy Soil Using Geosynthetic: An Experimental Study on Sand Types and Reinforcement Material Variations - Soehardi, Fitridawati; Hakam, Abdul; Thamrin, Rendy; Mera, Mas (Annales de chimie (Paris. 1914), 2025)
Sand is commonly used as a base material in construction; however, its non-cohesive nature and high deformability make it less ideal for directly supporting structural loads. One of the solutions developed to address this limitation is the use of geosynthetic materials for soil reinforcement. This study aims to analyze the influence of sand gradation (coarse, medium, fine) and types of geosynthetics (woven geotextile, non-woven geotextile, and geogrid) on the bearing capacity of sand, with geosynthetics placed at a fixed depth of 5 cm. The testing was conducted using a plate load test within a small-scale laboratory model box. Results indicate that the combination of coarse sand and geogrid produced the highest bearing capacity, increasing from 161.46 kg (unreinforced) to 261.63 kg. Woven and non-woven geotextiles also improved bearing capacity, albeit with lower effectiveness. The stress–strain graph shows that the use of geosynthetics enhances soil stiffness and reduces deformation. The ultimate bearing capacity versus settlement graph confirms that geogrid and woven geotextile are effective in maintaining structural performance up to a 1-inch settlement. Overall, geosynthetics proved to be effective, particularly in coarse sand, with a bearing capacity increase of up to 61.33%.